A Capability-Based Assessment of GVC Competitiveness for the SACU Region - Pathikonda, Vilas; Farole, Thomas (World Bank, Washington, DC, 2016)
The emergence of global value chains (GVCs) and their rapid expansion over the past two decades has transformed the global trade environment. GVCs involve task-based trade across multiple stages of the production process that take place across a number of different countries, in which multiple inputs and exports of intermediate goods and services are necessary to produce a final good, which may also be exported. GVC-oriented trade is seen to offer significant opportunities for developing countries, especially smaller ones, to benefit from global integration by changing the nature of competitiveness. With competition for GVC investment taking place in a truly global market, factor competitiveness relative to other countries matters a lot. In this context, the purpose of this note is to shed some light for policymakers, in this case specifically in the Southern African Customs Union (SACU) countries, on where to focus efforts to drive competitiveness for GVC participation. This is a data-intensive exercise that requires indicators to represent underlying capabilities, disaggregated international trade data, and finally, a classification of which products are likely to be trade within GVCs.